Comparative Evaluation of Essential Oils from Medicinal-Aromatic Plants of Greece: Chemical Composition, Antioxidant Capacity and Antimicrobial Activity against Bacterial Fish Pathogens - Anastasiou, Thekla I. (Molecules, 2019)
The administration of antibiotics in aquaculture has raised concern about the impact of their overuse in marine ecosystems, seafood safety and consumers’ health. This “green consumerism” has forced researchers to find new alternatives against fish pathogens. The present study focused on 12 Mediterranean medicinal-aromatic plants as potential antimicrobials and antioxidant agents that could be used in fish aquaculture. In vitro assays showed that the essential oils (EOs) from all studied plants had anti-bacterial and antioxidant properties, with their efficacy being dependent on their chemical composition. More specifically, EOs rich in carvacrol, p-cymene and γ-terpinene exhibited not only the strongest inhibitory activity against the growth of bacterial pathogens (inhibitory concentration: 26–88 μg mL(−1)), but also the greatest total antioxidant capacity (ABTS: 2591–5879 μmole mL(−1); CUPRAC: 931–2733 μmole mL(−1)). These compounds were mainly found in the EOs from Greek oregano (Origanum vulgare subsp. hirtum), Spanish oregano (Thymbra capitata) and savoury (Satureja thymbra) collected from cultivations in Greece. The specific EOs stand out as promising candidates for the treatment of bacterial diseases and oxidative stress in farmed fish. Further in vivo experiments are needed to fully understand the effects of EO dietary supplementation on fish farming processes.